A STUDY OF MALE AND FEMALE REFUSAL STRATEGY PERFORMED BY EMPLOYEES OF BCD TRAVEL INDONESIA - Yunia Pramadita Putri; Mangantar Sitohang (STIBA IEC JAKARTA, 2022)
The objectives of this research are to analyze what refusal strategies performed by male and female employees of BCD Travel Indonesia and to identify the language features found in refusal strategies of male and female employees. The qualitative method, specifically using a case study is used in this research. The primary data source of this study was taken from a written document namely Discourse Completion Test (DCT) proposed by Beebe and friends (1990) with little modification. Questionnaires to collect the data, specifically the Discourse Completion Test (DCT) as the instrument are applied in this research. The findings show that from 132 utterances of male employees, 80 utterances are indirect strategy, 28 utterances are adjuncts, and 24 utterances are direct strategy. These results show that male and female employees have their own ways of delivering indirect refusal strategy. In the utterances of male and female employee’s refusal strategies, 5 of 10 language features, such as lexical hedges or fillers, intensifiers, ‘superpolite’ forms, avoidance of strong swear words and emphatic stress are investigated. Keywords : Refusal strategies, language features, male and female employees